PROTEIN RESIDUE ANALYSIS, CHARCOAL IDENTIFICATION, AND AMS RADIOCARBON DATING OF BONE AND CHARCOAL FROM THE FRANCOIS PAULETTE CABIN SITE (2315R), WOOD BUFFALO NATIONAL PARK, ALBERTA, CANADA - Puseman, Kathryn (PaleoResearch Institute); Yost, Chad (PaleoResearch Institute); Logan, Melissa K. (PaleoResearch Institute) (the Digital Archaeological Record)
The Francois Paulette Cabin Site (2315R) site is a stratified, multi-component, precontact site located along the Slave River in Wood Buffalo National Park, northern Alberta. Charcoal and bone recovered from this site were submitted for identification and/or AMS radiocarbon dating. Eight radiocarbon dates were obtained from seven charcoal fragments and a partially burned antler fragment. Lithics recovered throughout the site also were submitted for protein residue analysis to provide information concerning animals that might have been hunted and/or processed with these tools.